2013
DOI: 10.5114/wo.2013.34621
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of FLT-PET/CT usefulness in diagnosis and qualification for surgical treatment of gastric cancer

Abstract: Aim of the studyEvaluation of FLT/PET/ CT usefulness in diagnosis and qualification for surgical treatment of gastric cancer.Material and methodsThe FLT/PET/CT test was carried out in a group of 50 gastric cancer patients. Based on the test result, a decision followed about the therapeutic procedure to be applied. A comparison was made with regards to the consistency of the cancer growth advancement degree evaluation in the initial preoperative FLT/PET/CT test against the evaluation of postoperative degree of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
6
1
Order By: Relevance
“…We notice that in women representation of grade 3 was slightly higher but due to small sample we could not prove statistical significance. Compared to other researchers such as one by Staniuk T. and associates ( 7 ) which found grade 2 in 12 patients and grade 3 in 13 patients and 25 patients did not specify the grade, we find that more than half of the patients in our group of patients had grade 3.…”
Section: Discussioncontrasting
confidence: 91%
“…We notice that in women representation of grade 3 was slightly higher but due to small sample we could not prove statistical significance. Compared to other researchers such as one by Staniuk T. and associates ( 7 ) which found grade 2 in 12 patients and grade 3 in 13 patients and 25 patients did not specify the grade, we find that more than half of the patients in our group of patients had grade 3.…”
Section: Discussioncontrasting
confidence: 91%
“…Because 18 F-FDG-PET showed false-positive uptake in areas of inflammation, Nakajo reported that 18 F-FLT-PET showed greater specificity in staging lymph nodes in gastrointestinal tumors compared to 18 F-FDG-PET [ 111 ]. Staniuk [ 112 ] evaluated local lymph node uptake in 22 patients with gastric cancer and identified one patient with micrometastasis. 18 FLT-PET/CT examination confirmed a lymph node metastasis rate of 73%.…”
Section: Potential Approaches For the Detection Of Olnm In Gastric Ca...mentioning
confidence: 99%
“…The aim of this evaluation was to compare uptake in normal and cancerous tissue in the stomach. The staging was described in our initial report published in June 2013 [ 5 ].…”
Section: Methodsmentioning
confidence: 99%